Hepatoprotective effects of Lactobacillus plantarum C88 on LPS/D-GalN–induced acute liver injury in mice - Cuicui Duan; Yujuan Zhao; Cheng Huang; Zijian Zhao; Lei Gao; Chunhua Niu; Chao Wang; Xiaoxiao Liu; Chuan Zhang; Shengyu Li (Journal of Functional Foods, 2018)
Acute liver failure (ALF) is a life-threatening clinical condition resulting from massive apoptosis of hepatocytes. This study aims to examine the protective effects of Lactobacillus plantarum C88 on LPS/D-GalN-induced ALF and elucidate its underlying molecular mechanisms in mice. The results showed that L. plantarum C88 pretreatment significantly reduced the levels of plasma ALT and AST in mice with LPS/D-GalN–induced liver injury. L. plantarum C88 pretreatment decreased the secretion of inflammatory cytokines. In addition, L. plantarum C88 remarkably increased the expression levels and nuclear translocations of Nrf2 mRNA in liver tissues, but inhibited NF-κB nuclear translocations and P65, P38 phosphorylation levels. Moreover, L. plantarum C88 enhanced the intestinal mucosal barrier by upregulating the expressions of tight junction proteins as well as HIF-1α. These results suggest that L. plantarum C88 protects against ALF associated with Nrf2 and the MAPK/NF-κB signaling pathways.